Penetapan Kadar Asam Lemak Bebas (Alb) Pada Minyak Goreng Kemasan Dan Minyak Goreng Curah Dengan Perlakuan Berdasarkan Lama Waktu Pemanasan - Khoirul Mahmudah; Vivin Nopiyanti (STIKES MUHAMMADIYAH KLATEN, 2019)
Cooking oil is one of the ingredients needed by the community, especially house wives and made from oi lpalm. Free fatty acids are not separated from cooking oil which causes bad effects on humans. This study aims to determine the levels of free fatty acids (FFA) in packagedcookingoilandbulkcookingoilbytreatmentbasedonheatingtime .This study uses the sample used in this study, bulk cooking oil taken from the markets of Mojosongo, Surakarta and 3 samples of packaged cooking oil which are sold in Surakarta Supermarket in January 2019. This research method uses acid base titration. The time used for analysisis 0 ', 15', 30 ', 45', 60 ', 75'at 160 and compares the levels with the Cooking Oil Quality Standards .The results of this study indicate the levels of free fatty acids in cooking oil, sample A heating to 0,1,2,3 was 0,16%; 0,20%; 0,22%; 0,25% according to SNI while heating to 4, 5 was 0,33%; 0,40% did not meet SNI standards. Sample B warmed up to 0,1,2,3,4,5 which were 0,12%; 0,14%; 0,15%; 0,17%; 0,21%; 0,24%, Sample C warmed up to 0,1,2,3,4,5 which were 0,12%; 0,16%; 0,19%; 0,21%; 0,22%; 0,24%; Sample D warms up to 0,1,2, 3,4,5 whichwere 0,12%; 0,14%; 0,16%; 0,18%; 0,21%; 0,24% according to the Cooking Oil Quality Standards.